Íslenskt orðanet: Et skritt mot en allmennspråklig onomasiologisk ordbok - Jónsson, Jón Hilmar; Úlfarsdóttir, Þórdís (LexicoNordica, 2011)
Íslenskt orðanet (Icelandic wordnet) is an ongoing project which aims to analyse and describe the Icelandic vocabulary and its internal relations from the onomasiological point of view. The source material is mainly derived from a comprehensive lexicographical description of Icelandic collocations and phrasemes. The semantic relations between words and other independent lexical units are traced and identified by revealing their syntactic relations, thus building up a lexicographical database with approx. 250,000 singleword and multi-word lemmas. The wordnet combines the roles of a synonym dictionary and a thesaurus, placing special emphasis on verbal constructions and other multi-word lexical units. Within the groups of semantically closely related words, the characteristic lexical and syntactic patterns of the individual words are compared, which gives clues to their degree of semantic relatedness.